Literature in the time of COVID-19: The "phase two". (October 2020) - Zocchi, Jacopo; Pietrobon, Giacomo; Moretto, Silvia; Bonsembiante, Anna; Mazzola, Francesco; Petruzzi, Gerardo; Iocca, Oreste; Pichi, Barbara; Ansarin, Mohssen; Pellini, Raul
Highlights: COVID-19 pandemics pushed a generous production of scientific literature. A bibliometric review of the top 20 valuable ENT journals was performed. Topics related to the effects of COVID-19 on the ENT practice have been exhausted. A step to quantitative research is desirable. Abstract: The sudden onset of the COVID-19 pandemic has put a strain on the whole scientific world. We assisted to a tremendous effort by researchers with the final goal of achieving a better management of COVID-19 patients. The world of otorhinolaryngology, likewise, has not been exempt from this commitment to research. In this commentary we perform a bibliometric review of the available academic literature about COVID-19 in the top 20-ranked ENT journal, with the goal of providing an overview of what has been published to date and encouraging a shift towards quantitative research.